(IN)CORRECT: Performance review: „(IN)CORECT”, Play and directing by Leta Popescu, stage design by Lucia Mărneanu, with Alexandra Caras, Cătălin Filip, Oana Mardare, Alina Mișoc, Emőke Pál, Paul Sebastian Popa, Lucian Teodor Rus, Doru Taloș. A production of Reactor de Creație și Experiment, Cluj-Napoca, România, 2020. - ȚÎRLEA, Ana Maria (Studia Universitatis Babeș-Bolyai Dramatica, 2021)
Cluj-Napoca, February 2020. The independent artistic team Reactor de Creație și Experiment continue their multiannual programme started in 2019, Decalaj. Narațiuni intergeneraționale (Gap. Intergenerational Narratives). This time, however, the project coincides with the last performance of the trilogy Colaj (Collage) by director Leta Popescu. Began at the Hungarian State Theatre Cluj in 2018 with the performance (In)vizibil (In/visible), a collage of texts on loneliness by Romanian and Hungarian contemporary authors, continued at the Timișoara National Theatre with (In)credibil (In/credible), a collage of the director’s own texts and writings on failure signed by Mihaela Michailov, Peca Ștefan, and Elise Wilk, Leta Popescu's directing project brings the collage closer to the concept of a “broken mirror” in which the spectator can identify as many perspectives as allowed by imagination. (In)corect marks the end of this search and the director’s debut as playwright.